2006
DOI: 10.1038/ng1755
|View full text |Cite
|
Sign up to set email alerts
|

Functional classification of drugs by properties of their pairwise interactions

Abstract: Multidrug treatments are increasingly important in medicine and for probing biological systems. Although many studies have focused on interactions between specific drugs, little is known about the system properties of a full drug interaction network. Like their genetic counterparts, two drugs may have no interaction, or they may interact synergistically or antagonistically to increase or suppress their individual effects. Here we use a sensitive bioluminescence technique to provide quantitative measurements of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
394
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 324 publications
(431 citation statements)
references
References 29 publications
33
394
4
Order By: Relevance
“…Those studies concluded that the vast majority of three-way interactions are additive or can be predicted from pairwise interactions. This important difference in results and conclusions is likely because neither of these previous studies performed a rescaling based on maximum entropy or other methods to set a baseline expectation for synergy or antagonism as done here or in previous pairwise studies [35,38]. Indeed, some of us recently re-analysed Wood et al's data using a few rescaling methods and did find the existence of several higher-order emergent interactions [48].…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Those studies concluded that the vast majority of three-way interactions are additive or can be predicted from pairwise interactions. This important difference in results and conclusions is likely because neither of these previous studies performed a rescaling based on maximum entropy or other methods to set a baseline expectation for synergy or antagonism as done here or in previous pairwise studies [35,38]. Indeed, some of us recently re-analysed Wood et al's data using a few rescaling methods and did find the existence of several higher-order emergent interactions [48].…”
Section: Discussionmentioning
confidence: 93%
“…Our method for determining the type of three-way interaction follows previous work [35,38]. To calculate our rescaled three-way interaction measures, we use the median of replicate measurements for each experiment at a single antibiotic concentration.…”
Section: Cut-off Values For Determining Three-way Interaction Typesmentioning
confidence: 99%
See 3 more Smart Citations